Premorbid obesity, but not nutrition, prevents critical illness‐induced muscle wasting and weakness. Issue 1 (20th July 2016) - Goossens, Chloë; Marques, Mirna Bastos; Derde, Sarah; Vander Perre, Sarah; Dufour, Thomas; Thiessen, Steven E.; Güiza, Fabian; Janssens, Thomas; Hermans, Greet; Vanhorebeek, Ilse; De Bock, Katrien; Van den Berghe, Greet; et al.
Abstract: Background: The 'obesity paradox' of critical illness refers to better survival with a higher body mass index. We hypothesized that fat mobilized from excess adipose tissue during critical illness provides energy more efficiently than exogenous macronutrients and could prevent lean tissue wasting. Methods: In lean and premorbidly obese mice, the effect of 5 days of sepsis‐induced critical illness on body weight and composition, muscle wasting, and weakness was assessed, each with fasting and parenteral feeding. Also, in lean and overweight/obese prolonged critically ill patients, markers of muscle wasting and weakness were compared. Results: In mice, sepsis reduced body weight similarly in the lean and obese, but in the obese with more fat loss and less loss of muscle mass, better preservation of myofibre size and muscle force, and less loss of ectopic lipids, irrespective of administered feeding. These differences between lean and obese septic mice coincided with signs of more effective hepatic fatty acid and glycerol metabolism, and ketogenesis in the obese. Also in humans, better preservation of myofibre size and muscle strength was observed in overweight/obese compared with lean prolonged critically ill patients. Conclusions: During critical illness premorbid obesity, but not nutrition, optimized utilization of stored lipids and attenuated muscle wasting and weakness.